Effect of Interdependency among Supplier Selection Criteria on Supplier Selection in the Automotive Industry - Kasirian, Mohammadnavid (2009)
Most organizations prefer to outsource their activities which are not cost-efficient. The proper supplier selection requires all criteria to be clearly identified and investigated. Previous studies indicate that interdependencies exist among the criteria of supplier selection, and this may have an effect on the rankings of suppliers. In this study, six criteria for supplier selection (Cost, Quality, Delivery Reliability, Flexibility and Responsiveness, Professionalism, and Long-Term Relationship) were identified through literature and the interdependencies among them were investigated. A questionnaire was developed to identify weights for the criteria and sub-criteria of supplier selection and to identify the interdependencies among them. One set of this questionnaire was sent to three companies (two in Malaysia and one in Iran) related to automotive industry. Five expert decision makers in each Malaysian company answered the questionnaire and six in Iran. The supplier selection evaluation was done under two conditions, with and without considering interdependencies. An Analytic Hierarchy Process (AHP) method was used when the criteria were assumed independent. For interdependencies, Analytic Network Process (ANP) and a hybrid Modified TOPSIS (Technique for Order Performance by Similarity to Ideal Solution) were used. A trial version of Super Decisions 1.6.0 software was used to develop all the three methods. The optimal ordering quantity was then determined by means of a multi-objective decision making (MODM) technique named Preemptive Goal Programming (PGP) aimed to maximize the Total Value of Purchasing (TVP) and to minimize the Total Cost of Purchasing (TCP) using a trial version of Win QSB 1.0 as a linear programming software. Findings from the model show that by considering the interdependencies, the optimal ordering quantities have been changed. Based on this fact, in all three companies the hybrid Modified TOPSIS is more effective than ANP and AHP methods. The results for PROTON show that the hybrid Modified TOPSIS had the optimal TVP of 2,542 units, while the values for AHP and ANP were 1,609 and 1,515 units respectively. However, all three methods present the TCP value of 306,575 US Dollars. This trend was also seen in the other two companies. The results showed that interdependencies existed among the criteria and they influence the decision of supplier selection. The study was conducted for one particular product. Similar methods can be used to identify the best supplier selection with other products and other manufacturing industries.